Media and breastfeeding: Friend or foe? - Brown, Jane D (BioMed Central, 2008)
The mass media have the potential to be powerful friends or foes in promoting breastfeeding. The media could help by putting the issue of breastfeeding on policy agendas and by framing breastfeeding as healthy and normative for baby and mother. Currently, however, it looks as if the media are more often contributing to perceptions that breastfeeding is difficult for mothers and potentially dangerous for babies. This paper presents a brief overview of research on the media and breastfeeding, some insights into the market forces and human psychological factors that may play into media representations of breastfeeding, and strategies to help breastfeeding advocates work more effectively with the media.